Silicon-based solid-state battery and preparation method thereof

By modifying nano-silicon and combining with porous membrane materials and combining with ultrasonic-assisted charging and discharging technology, the problem of volume expansion and poor conductivity of silicon-based solid-state batteries is solved, and the capacity performance, low temperature stability and fast charging performance are significantly improved.

CN119764579AActive Publication Date: 2025-04-04DALI CHENYU ENERGY STORAGE NEW MATERIALS CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411736659.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

Due to problems such as large volume expansion and poor conductivity, silicon-based solid-state batteries are difficult to effectively exert their theoretical capacity, and their performance is poor under low temperature and high magnification conditions.

Method used

By modifying the nano-silicon and combining it with porous membrane material, an ultrasonic-assisted first-circle charge and discharge process is used to optimize the interface structure and conductivity.

Benefits of technology

The capacity performance, low-temperature cycle stability and fast charging performance of silicon-based solid-state batteries have been significantly optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764579A_ABST
    Figure CN119764579A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of solid-state batteries, and particularly relates to a preparation method of a silicon-based solid-state battery, which comprises the following steps: carrying out modification treatment on nano silicon in a modification solution containing a formula 1 # imgabs0 # compound to prepare modified nano silicon; compounding the modified nano silicon serving as a negative electrode active material on a current collector to form a silicon negative electrode; soaking the porous membrane material in a precursor solution of a formula 2 # imgabs1 # azo compound and an organic lithium salt to obtain a liquid-absorbing porous membrane material; a positive electrode, a liquid absorption porous membrane material and the silicon negative electrode are compounded to form a battery cell, first-circle charging and discharging are carried out after packaging, the silicon-based solid-state battery is prepared, and the charging process of the first-circle charging and discharging is carried out under the assistance of ultrasonic waves. The invention also comprises the solid-state battery prepared by the method. According to the method, the low-temperature cycling stability and the high-rate performance of the silicon-based solid-state battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solid electrode negative electrode preparation, and specifically relates to the field of silicon negative electrode for silicon-based solid-state batteries. Background Art

[0002] The silicon negative electrode has excellent performance such as capacity, but it also has problems such as large volume expansion and poor conductivity. This disadvantage of the silicon negative electrode will be further amplified in the solid-state battery system, which will further increase the difficulty of adapting the silicon negative electrode to the solid-state battery.

[0003] To address this problem, there are some improvement methods in the existing technology, mainly focusing on lithium insertion, coating and structural optimization of silicon negative electrodes. For example:

[0004] The Chinese patent document with publication number CN119008858A discloses a porous silicon-carbon negative electrode for solid-state batteries, wherein the porous silicon-carbon negative electrode includes a negative electrode active material layer, wherein the negative electrode active material layer includes porous silicon carbon, conductive carbon black and a binder, wherein the binder includes at least one of polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile and carboxymethyl cellulose. The Chinese patent document with publication number CN118943319A discloses a lithium molybdate-coated silicon negative electrode material and its preparation method and application, wherein the lithium molybdate-coated silicon negative electrode material has a core-shell structure, wherein the core includes silicon powder and the shell includes lithium molybdate. The patent document with publication number CN221994503U discloses a solid-state battery silicon negative electrode sheet, wherein the silicon negative electrode sheet includes a negative electrode current collector, a conductive carbon layer, a lithium metal layer and a silicon negative electrode active layer stacked in sequence, wherein the silicon negative electrode active layer is provided with a concave-convex pattern on the surface of the side away from the negative electrode current collector. A Chinese patent document with publication number CN118888690A discloses a composite lithium metal negative electrode sheet, a preparation method and an application. The composite lithium metal negative electrode sheet includes a substrate in a sheet shape with a front side and a back side; a lithium metal layer covering the front side and the back side of the substrate; and a nano silicon layer attached to the lithium metal layer.

[0005] In summary, there are some improvements in the existing technology to improve the adaptation of silicon negative electrodes to solid-state battery systems, but the means of improvement are still relatively scarce, and it is difficult to fundamentally solve the problems caused by low conductivity and high expansion of silicon, especially it is difficult to effectively improve the capacity utilization rate, low temperature stability and unsatisfactory fast charging performance of solid-state batteries. Summary of the invention

[0006] In response to the problems existing in solid-state silicon-based solid-state batteries, the first purpose of the present invention is to provide a method for preparing a silicon-based solid-state battery, aiming to prepare a solid-state silicon-based battery that has excellent capacity utilization, low-temperature stability and fast charging performance.

[0007] The second purpose of the present invention is to provide a silicon-based solid-state battery produced by the preparation method.

[0008] Silicon-based solid-state batteries have more prominent problems such as large volume expansion and low conductivity, making it difficult to effectively exert their theoretical capacity and difficult to adapt to application requirements under low temperature and high rate conditions. To address this problem, the present invention has provided the following improvement scheme after research:

[0009] A method for preparing a silicon-based solid-state battery comprises modifying nano-silicon in a modifying solution containing a compound of formula 1 to obtain modified nano-silicon;

[0010]

[0011] The R 1 C 1 ~C 6 or

[0012] The R 2 ~R 4 Alone for C 1 ~C 6 ; The R 5 , R 6 H or C alone 1 ~C 6 ;

[0013] Using modified nano-silicon as negative electrode active material and compounding it on the current collector to form a silicon negative electrode;

[0014] Soaking the porous membrane material in a precursor solution of formula 2, an azo compound, and an organic lithium salt to obtain a liquid-absorbing porous membrane material;

[0015]

[0016] The R 7 H, C 1 ~C 6 An alkyl group or a substituted alkyl group; the substituted alkyl group is an alkyl group containing at least one of a hydroxyl group, an amino group, and an ester group;

[0017] The positive electrode, the liquid-absorbing porous membrane material and the silicon negative electrode are composited to form a battery core, which is packaged and then charged and discharged for the first time to obtain the silicon-based solid-state battery, wherein the charging process of the first charge and discharge is performed under the assistance of ultrasound.

[0018] The present invention innovatively pre-modifies the nano-silicon material with the component of formula 1, and then assembles it with a porous membrane material that absorbs a precursor solution of the formula 2 and an azo compound to form a battery, and performs the first cycle charging under the assistance of ultrasound. This can facilitate the mechanical effect of the volume expansion of the silicon negative electrode in combination with ultrasound, improve the hierarchical interface between materials, reduce interface impedance, and release expansion space, thereby significantly optimizing the capacity utilization of the material and improving the low-temperature cycle stability and high-rate performance of the silicon-based solid-state battery.

[0019] In the present invention, the nano-silicon modification process, the precursor solution composition, and the in-situ curing of the dual effects of ultrasound and silicon negative electrode expansion mechanical action are the key to optimizing interface action, reducing interface impedance, unblocking expansion space, and improving the capacity release rate, low temperature stability and fast charging performance of the material.

[0020] In the present invention, nano-silicon is modified in advance by the formula 1, and then combined with subsequent processes, which can help improve the interface impedance of the solid-state battery, build a suitable conductivity, and further help improve the capacity utilization rate, low-temperature cycle stability and fast charging performance of the prepared silicon-based solid-state battery.

[0021] In the present invention, the formula 1 includes formula 1A and / or formula 1B;

[0022]

[0023] Preferably, the formula 1 is a composite of formula 1A and formula 1B, and more preferably, the weight ratio of the formula 1A to the formula 1B is 5 to 20: 100. The present invention shows that under the preferred formula 1A and formula 1B, it is helpful to further optimize the surface structure of nano-silicon, to further combine with subsequent modification processes, and to further improve the capacity utilization rate, low temperature cycle stability and fast charging performance of the prepared silicon-based solid-state battery.

[0024] In the present invention, the weight ratio of nano silicon to the compound of formula 1 is 2-5:100.

[0025] Preferably, the D50 of nano-silicon is 20-300 nm.

[0026] In the present invention, the modified nano-silicon can be used as the negative electrode active material based on conventional means to prepare the required silicon negative electrode. For example, the negative electrode material of the silicon negative electrode also contains a conductive agent and a binder. In the negative electrode material, the content of nano-silicon is 70-90wt.%. The surface loading of the silicon negative electrode is 0.5-2mg / cm 2 .

[0027] In the present invention, Formula 2 and azo compounds are innovatively used to pre-modify the porous membrane material, and then combined with the subsequent ultrasonic first-cycle charging treatment. In this way, based on the dual effects of ultrasound and the expansion mechanical effect of the silicon material itself, the interface structure and ion-electron conduction network can be optimized in situ, thereby optimizing the capacity utilization rate, low-temperature cycle stability and fast charging performance of the prepared silicon-based solid-state battery.

[0028] In the present invention, the azo compound includes at least one of azobisisobutyronitrile and azobisisoheptanenitrile.

[0029] The organic lithium salt may be any conductive lithium salt in the industry, for example, at least one of lithium bis(oxalatoborate), lithium trifluoromethanesulfonyl imide, and lithium bis(fluorosulfonyl imide).

[0030] Preferably, the weight ratio of the compound of formula 2 and the azo compound is 20-100:1 (or 40-60:1), wherein the concentration of the organic lithium salt in the precursor solution is 0.5-5M (or 0.7-1.5M).

[0031] Preferably, the precursor solution further comprises a component of formula 3;

[0032] The present invention shows that adding the formula 3 to the precursor solution can further cooperate with the silicon first expansion and ultrasonic dual combined process to further optimize the capacity utilization, low-temperature cycle stability and fast charging performance of silicon-based solid-state batteries.

[0033] Preferably, the weight of Formula 3 is 5-20% of Formula 2.

[0034] In the present invention, the porous membrane material is a glass fiber membrane.

[0035] Preferably, the weight ratio of the porous membrane material to the precursor solution is 1:0.3-0.8.

[0036] In the present invention, the positive electrode may be a positive electrode known in the industry, for example, a commercial positive electrode, or may be prepared based on conventional principles and means.

[0037] For example, the positive electrode includes a current collector and a positive electrode material composited on its surface, wherein the positive electrode material includes a positive electrode active material containing lithium, preferably including at least one of lithium iron phosphate, binary material, and ternary material. The binary material is a lithium-containing or sodium-containing salt containing two elements of Ni, Co, Mn, and Al. The ternary material is a lithium-containing or sodium-containing salt containing three elements of Ni, Co, Mn, and Al. In addition, trace elements are allowed to exist in the positive electrode active material.

[0038] Preferably, the capacity ratio of the positive electrode to the silicon negative electrode is 1.05 to 1.4:1.

[0039] In the present invention, after the battery is assembled into the battery, it is charged under ultrasound, so that an excellent interface can be constructed based on the combination of ultrasound and the mechanical action of the first cycle of silicon-based materials, thereby optimizing the capacity utilization rate, low-temperature cycle stability and fast charging performance of the prepared silicon-based solid-state battery.

[0040] In the present invention, the power, temperature and current in the first cycle charging stage are further optimized, which helps to further improve the capacity utilization, low-temperature cycle stability and fast charging performance of the prepared silicon-based solid-state battery.

[0041] Preferably, the power of ultrasound is 500-1000W.

[0042] Preferably, the temperature in the first cycle charge and discharge stage is 50-60°C.

[0043] Preferably, the current in the first cycle charge and discharge stage is 1-5 mA / cm2.

[0044] The cut-off voltage for charge and discharge is 2.75~4V.

[0045] In the present invention, the preferred solution is that the first cycle charging includes two stages of ultrasonic assisted processing, wherein the power of the first stage of ultrasonic assisted is 500-700 W, and the power of the second stage of ultrasonic assisted is 800-1000 W. In the present invention, based on the two-stage gradient ultrasonic assisted charging, it can be further based on the combination of ultrasound and silicon in-situ expansion, which helps to further synergistically optimize the interface and further optimize the low-temperature fast charging performance of the obtained silicon-based solid-state battery.

[0046] In the present invention, the first stage of ultrasound-assisted charging is performed to 40-60% of the power.

[0047] In the present invention, the first-cycle discharge process in the first-cycle charge and discharge stage may be performed under ultrasound or not under ultrasound.

[0048] The present invention also includes a silicon-based solid-state battery prepared by the preparation method.

[0049] The preparation method of the present invention can give the prepared silicon-based solid-state battery special physical and chemical characteristics, and the silicon-based solid-state battery prepared by the preparation method can improve capacity utilization, low-temperature cycle stability and fast charging performance.

[0050] Beneficial effects:

[0051] The present invention can significantly optimize the interface structure of silicon-based solid-state batteries through the modification of nano-silicon and the combined modification of the precursor solution of the porous mold, and further cooperate with the mechanical action of ultrasound and silicon-based in-situ expansion, which helps to improve the capacity utilization, low-temperature cycle stability and fast charging performance of silicon-based solid-state batteries.

[0052] The present invention also shows that adding a certain amount of Formula 3 to the precursor solution, and / or cooperating with the first cycle charging treatment of the gradient ultrasonic power, can help to further optimize the interface and improve the low temperature and fast charging performance of the prepared silicon-based battery. DETAILED DESCRIPTION

[0053] The present invention will be described in detail below with reference to the embodiments, but the present invention is not limited thereto.

[0054] In the present invention, the nano-silicon may be a nano-silicon material that can be used in solid-state batteries. For example, as an optional solution, the D50 of the nano-silicon may be 150±10 nm.

[0055] Example 1

[0056] Step 1: Silicon Modification

[0057] Pretreat the nano-silicon. Disperse the nano-silicon in anhydrous ethanol, add the pre-treatment agent: a mixture of Formula 1A: Formula 1B = 20:100 while stirring, and the ratio of the pre-treatment agent to the nano-silicon is 3:100. Stir for 5 minutes after dropping, then centrifuge at 8000-12000 rpm to separate the silicon, and then vacuum dry to obtain the pre-treated silicon.

[0058] Step 2:

[0059] The negative electrode of nano silicon was prepared by common method, and the surface loading of nano silicon was 1.5±0.1mg / cm2. The positive electrode was prepared by commercial positive electrode material. The positive and negative electrode capacity ratio was 1.2:1.

[0060] Negative electrode: negative electrode active material (modified nano silicon in step 1), conductive agent SP, binder LA-133, CMC are weighed in a ratio of 90:5:3:2 for standby use. After dry grinding the weighed negative electrode active material, SP and CMC in an agate mortar for a certain period of time, LA-133 and appropriate amount of deionized water are added and wet grinding is continued for a certain period of time to obtain a homogeneous slurry material. Cut the current collector (copper foil) into long sheets of appropriate size, wipe both surfaces clean with alcohol, and lay the smooth surface down on the automatic coating machine. After spraying an appropriate amount of alcohol, gently wipe the current collector with filter paper until it is flat. After the alcohol evaporates, transfer the slurry to the current collector in a narrow and long manner, and then use a scraper to evenly coat it into a sheet so that the slurry is evenly attached to the surface of the current collector; carefully transfer the coated pole piece to an oven (80°C) for drying for 12 hours for standby use.

[0061] Positive electrode: The positive electrode active material (NCM111), conductive carbon black SP, and binder (PVDF) were weighed in a mass ratio of 8:1:1, and fully ground in an agate mortar (dry grinding first, then adding solvent for wet grinding) to make a homogeneous slurry material; the current collector (aluminum foil) was cut into long sheets of suitable size, both surfaces were wiped clean with alcohol, and laid flat on a flat glass with the glossy surface facing down, sprayed with an appropriate amount of alcohol, and then gently wiped the current collector with filter paper until it was flat. After the alcohol evaporated, the slurry was transferred to the top of the current collector in a narrow and long manner, and then a scraper was used to evenly spread it into a sheet so that the slurry was evenly attached to the surface of the current collector; the coated electrode was carefully transferred to an oven (120°C) for drying for 12 hours for use.

[0062] Liquid-carrying glass fiber membrane: n-butyl acrylate, azobisisobutyronitrile, and lithium trifluoromethanesulfonyl imide are mixed evenly to obtain a precursor solution, wherein the weight ratio of n-butyl acrylate to azobisisobutyronitrile is 40:1, and the concentration of lithium trifluoromethanesulfonyl imide is 1M; then the glass fiber membrane is completely immersed in the mixed solution for 1 hour to obtain a liquid-carrying glass fiber membrane. The weight ratio of the glass fiber membrane to the precursor solution is 1:0.4;

[0063] Step 4:

[0064] The negative electrode plate, the liquid-carrying glass fiber membrane, the positive electrode plate and the commercial nickel foam gasket in the above step 3 are stacked in sequence to form a button battery.

[0065] Step 5: Formation

[0066] Place the above-mentioned battery in a constant temperature box at 50-60℃, pass a current of 2mA / cm2 for charge and discharge (the charge and discharge cut-off voltage is 2.75~4V), wherein the first charging stage is carried out under the assistance of ultrasound, wherein the power of the ultrasound is 600W, and the first discharging stage is not carried out under the assistance of ultrasound, and the required new silicon electrode solid-state battery can be obtained.

[0067] Step 6:

[0068] The solid-state battery in step 5 was tested at 25°C and -15°C, with a test current rate of 0.25C and a voltage range of 2.75 to 4V. A rate charge and discharge test was performed at 25°C with a test current rate of 2.5C.

[0069] Example 2

[0070] Compared with Example 1, the only difference is that the treatment agent in step 1 is changed. The experimental groups are:

[0071] Group A: The treatment agent is Formula 1A, and the amount of the treatment agent and other conditions are the same as those in Example 1;

[0072] Group B: The treatment agent is Formula 1B, and the amount of the treatment agent and other conditions are the same as in Example 1.

[0073] Example 3

[0074] Compared with Example 1, the only difference is that in step 5, the ultrasonic conditions are changed, and the experimental groups are:

[0075] Group A: The ultrasonic power was set to 900 W, and other operating conditions were the same as those in Example 1;

[0076] Group B: charged to half of the capacity at 600 W, and then charged to the cut-off voltage at 900 W. Other operations and parameters are the same as those in Example 1.

[0077] Example 4

[0078] Compared with Example 1, the only difference is that in step 3, the compound of formula 3 is further added to the precursor solution, and the added amount is 10% of the weight of n-butyl acrylate. Other operations and parameters are the same as in Example 1.

[0079] Example 5

[0080] Compared with Example 1, the only difference is that in step 1, the ratio of the pretreatment agent to the nano-silicon is 5:100 in the mixed solution of Formula 1A: Formula 1B = 30:100. The treatment time is 10 minutes; in step 2, the precursor solution is a solution of propyl acrylate, azobisisobutyronitrile, and lithium trifluoromethanesulfonyl imide, wherein the weight ratio of propyl acrylate to azobisisobutyronitrile is 50:1; the concentration of lithium trifluoromethanesulfonyl imide is 0.8M; and then the glass fiber membrane is completely immersed in the mixed solution for 1.5 hours. The weight ratio of the glass fiber membrane to the precursor solution is 1:0.6. Other operations and parameters are the same as in Example 1.

[0081] Comparative Example 1

[0082] Compared with Example 1, the only difference is that step 1 is not performed, and nano-silicon is directly used as a raw material for subsequent treatment. Other operations and parameters are the same as those in Example 1.

[0083] Comparative Example 2

[0084] Compared with Example 1, the only difference is that in step 5, ultrasonic treatment is not performed.

[0085] The test results of step 6 of each case are shown in Table 1:

[0086] Table 1

[0087]

[0088] Note: (a): The number of cycles mentioned refers to the number of cycles when the capacity decays to 80% of the first cycle capacity;

[0089] (b): The number of cycles mentioned refers to the number of cycles in which the capacity decays to 80% of the initial capacity;

[0090] It can be seen from the examples and comparative examples that by modifying the nano-silicon and the combined modification of the precursor solution of the porous membrane, and further coordinating the combination of ultrasound and the mechanical action of silicon-based in-situ expansion, the interface structure of the silicon-based solid-state battery can be significantly optimized, which helps to improve the silicon-based solid-state battery. It can improve the capacity utilization rate, low-temperature cycle stability and fast charging performance. It can be seen from Examples 1 and 2 that the combined formula 1A and formula 1B can be combined with the subsequent ultrasonic-silicon-based self-mechanical combined action to optimize the interface, improve the capacity utilization rate of the silicon-based solid-state battery, and improve the low temperature and fast charging performance. In addition, it can be seen from Examples 1 and 3B that the use of the gradient ultrasound-assisted silicon-based in-situ expansion double can help to further strengthen the interface characteristics of the prepared material, help to further strengthen the capacity utilization rate of the prepared material, and improve its low temperature and fast charging performance. In addition, it can be seen from Examples 1 and 4 that adding a certain formula 3 to the precursor solution can cooperate with the combined action of the silicon in-situ machinery and ultrasound, which helps to further optimize the interface structure and further optimize the performance of the obtained silicon-based solid-state battery.

Claims

1. A method for preparing a silicon-based solid-state battery, characterized in that: Modifying nano silicon in a modification solution containing a compound of formula 1 to obtain modified nano silicon; The R1 is a C1-C6 alkyl group, or The R2 to R4 are independently C1 to C6; the R5 and R6 are independently H or C1 to C6; Using modified nano-silicon as negative electrode active material and compounding it on the current collector to form a silicon negative electrode; Soaking the porous membrane material in a precursor solution of formula 2, an azo compound, and an organic lithium salt to obtain a liquid-absorbing porous membrane material; The R7 is H, C1-C6 alkyl or substituted alkyl; the substituted alkyl is an alkyl containing at least one of hydroxyl, amino and ester groups; The positive electrode, the liquid-absorbing porous membrane material and the silicon negative electrode are composited to form a battery core, which is packaged and then charged and discharged for the first time to obtain the silicon-based solid-state battery, wherein the charging process of the first charge and discharge is performed under the assistance of ultrasound.

2. The method for preparing a silicon-based solid-state battery according to claim 1, characterized in that: The formula 1 includes formula 1A and / or formula 1B; Preferably, the weight ratio of nano-silicon to the compound of formula 1 is 2 to 5:100; Preferably, the D50 of nano-silicon is 20-300 nm.

3. The method for preparing a silicon-based solid-state battery according to claim 1, characterized in that: The negative electrode material of the silicon negative electrode also includes a conductive agent and a binder; Preferably, in the negative electrode material, the content of nano-silicon is 70-90wt.%; Preferably, the surface loading of the silicon negative electrode is 0.5 to 2 mg / cm 2 .

4. The method for preparing a silicon-based solid-state battery according to claim 1, characterized in that: The organic lithium salt includes at least one of lithium bis(oxalatoborate), lithium trifluoromethanesulfonyl imide and lithium bis(fluorosulfonyl imide); Preferably, the azo compound includes at least one of azobisisobutyronitrile and azobisisoheptanenitrile; Preferably, the porous membrane material is a glass fiber membrane; Preferably, the weight ratio of the formula 2 and the azo compound is 20 to 100:1, wherein the concentration of the organic lithium salt in the precursor solution is 0.5 to 5 M; Preferably, the precursor solution further comprises a component of formula 3; Preferably, the formula 3 is 5-20% by weight of the formula 2; Preferably, the weight ratio of the porous membrane material to the precursor solution is 1:0.3-0.

8.

5. The method for preparing a silicon-based solid-state battery according to claim 1, characterized in that: The positive electrode comprises a current collector and a positive electrode material composited on the surface thereof, wherein the positive electrode material comprises a positive electrode active material containing lithium, preferably at least one of lithium iron phosphate, a binary material, and a ternary material; Preferably, the capacity ratio of the positive electrode to the silicon negative electrode is 1.05 to 1.4:

1.

6. The method for preparing a silicon-based solid-state battery according to claim 1, characterized in that: The power of ultrasound is 500~1000W.

7. The method for preparing a silicon-based solid-state battery according to claim 1, characterized in that: The temperature during the first cycle of charge and discharge is 50-60°C.

8. The method for preparing a silicon-based solid-state battery according to claim 1, characterized in that: The current in the first cycle of charge and discharge is 1~5mA / cm2; the cut-off voltage is 2.5~4V.

9. The method for preparing a silicon-based solid-state battery according to any one of claims 1 to 8, characterized in that: The first round of charging includes two ultrasonic-assisted processing processes, in which the power of the first ultrasonic-assisted process is 500-700W, and the power of the second ultrasonic-assisted process is 800-1000W.

10. A silicon-based solid-state battery prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Composite lithium metal negative plate, preparation method and application

    CN118888690A

  • Lithium molybdate coated silicon negative electrode material as well as preparation method and application thereof

    CN118943319A

  • Porous silicon carbon negative electrode, solid-state battery and preparation method

    CN119008858A

  • Solid-state battery silicon negative plate and solid-state battery

    CN221994503U

  • Lithium ion battery quick charging assistance method and device based on external ultrasonic field

    CN111554988A